Sistem pakar penasihat persaraan / Zirwatul Hanan Salleh - Zirwatul Hanan, Salleh (2003)
Human is Allah’s servants who have intelligence. We have the ability to make assessment. However, human’s intelligence is limited. In computer sciences, the computer was first made to imitate human brain. It was also created to imitate human thinking and how we solve problem. Retirement advisor is built to consult people like a human expert. This system deploys the expert system concept which is a distinct character of artificial intelligence that differentiates it from conventional program. This retirement advisor will be developed using Visual Prolog programming language. It is with hope that this system will meet users requirement and satisfy their needs.